Application of Astrological Idioms to Twelve Tone Series Technique: Composition “BEYOND 12” - Rafael Dimas Prabowo; Puput Pramuditya; Nugrahanstya Cahya Widyanta (Universitas Negeri Surabaya, 2026)
This study integrates astrological idioms into musical composition using the twelve-tone series technique. The connection between the two is based on the similarity in the number of variables—namely 12—as well as the principle of equality. In the twelve-tone series, all 12 notes are treated equally without any tonal hierarchy, while in astrology, the ecliptic circle is divided into 12 zodiac signs with equal angles. The creative process includes idea formulation, title determination, literature review, and concept development before being realized in a musical composition. The method used is correlative exploratory and implementation, linking variables to form the basis of serialist composition. The creative strategy follows the movement patterns of the sun and moon in the ecliptic, which is divided into 4 quadrants. These quadrants serve as the foundation for the number of movements and series transformations. The melody in each movement is arranged according to zodiac groups, corresponding to their elements and angles within the geocentric cycle of the sun’s and moon’s movement.